2016
DOI: 10.1097/md.0000000000004146
|View full text |Cite
|
Sign up to set email alerts
|

Positron emission tomography and computed tomography angiography for the diagnosis of giant cell arteritis

Abstract: The use of 18F-fluoro-deoxyglucose positron emission tomography scan (FDG-PET) and computed tomography angiography (CTA) to improve accuracy of diagnosis of giant cell arteritis (GCA) is a very important clinical need. We aimed to compare the diagnostic performance of FDG-PET and CTA in patients with GCA.FDG-PET and CTA were acquired in all consecutive patients suspected for GCA. Results of FDG-PET and CTA were compared with the final diagnosis based on clinical judgment, temporal artery biopsy (TAB) findings,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
89
0
9

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 116 publications
(98 citation statements)
references
References 16 publications
0
89
0
9
Order By: Relevance
“…One study found 18F-fluoro-deoxyglucose uptake by large vessels yielded a sensitivity of 66.7% and a specificity of 100% for giant cell arteritis diagnosis 11. However, these patients either had a known diagnosis of the condition or were already suspected of having it.…”
Section: Discussionmentioning
confidence: 99%
“…One study found 18F-fluoro-deoxyglucose uptake by large vessels yielded a sensitivity of 66.7% and a specificity of 100% for giant cell arteritis diagnosis 11. However, these patients either had a known diagnosis of the condition or were already suspected of having it.…”
Section: Discussionmentioning
confidence: 99%
“…PET/CT is also a useful diagnostic tool for evaluating GCA. PET/CT is known to have a sensitivity of 89.5% and a specificity of 97.7% in GCA diagnoses 11) . Typically, the diagnosis of GCA was based on the presence of high FDG uptake in the vascular wall of the aorta, the supra-aortic branches, and the vertebral, iliac, and femoral arteries 11) .…”
Section: Discussionmentioning
confidence: 99%
“…Typically, the diagnosis of GCA was based on the presence of high FDG uptake in the vascular wall of the aorta, the supra-aortic branches, and the vertebral, iliac, and femoral arteries 11) . In GCA patients, CT angiography has proven to be effective in showing aortitis, which is characterized by thickening of the vessel wall, inflammatory periaortic soft tissue change, stenosis, or aneurysm 11) . Shoulder pain is a common problem in the elderly.…”
Section: Discussionmentioning
confidence: 99%
“… Data on computed tomography angiography (CTA) were from 1 study, using clinical diagnosis as the reference standard . …”
Section: Overview Of Existing Imaging Technologies For the Diagnosis mentioning
confidence: 99%